Dorsal root ganglion stimulation for refractory post‐herpetic neuralgia. Issue 7 (3rd May 2021) - Kim, Jung H.; Apigo, Anthony; Fontaine, Camille
Abstract: Post‐herpetic neuralgia is a chronic neuropathic pain disorder that is the sequela of the varicella zoster virus reactivation in the dorsal root ganglion. A variety of treatment modalities have been implemented, but pharmacologic treatments are often limited due to side effects and interventional procedures have yielded mixed results without promising long‐term benefits being consistently seen. A dorsal root ganglion stimulator for treatment of post‐herpetic neuralgia is a novel treatment option as it is able to specifically target the area affected. We present 3 patients who underwent implantation of permanent dorsal root ganglion stimulators and had a greater than 50% decrease in scoring on numerical rating scale (NRS) up to 18 months post‐procedure and significantly reduced analgesic requirements.